KOMPETENSI PROFESIONAL GURU YANG BERSERTIFIKASI DAPAT MENINGKATKAN PRESTASI BELAJAR SISWA - Endang Pristiawaty (Universitas Negeri Medan, 2015)
Essential competencies professorship is professional competence, socialcompetence, and personal competence. Professional competency, competence inthe field of substance or field of study, competence areas of learning, teachingmethods, assessment systems, the value of education and guidance. Socialcompetence, competence in the field of relationship and service, communityservice. Personal competence, competence value built through behaviors thatteachers, has a personal and attractive appearance, impressive and teachersslang and